Uveitis as a Risk Factor for Developing Acute Myocardial Infarction in Ankylosing Spondylitis: A National Population-Based Longitudinal Cohort Study - Lai, Yi-Fen; Lin, Ting-Yi; Chien, Wu-Chien; Sun, Chien-An; Chung, Chi-Hsiang; Chen, Yi-Hao; Chen, Jiann-Torng; Chen, Ching-Long (Frontiers in Immunology, 2022)
Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease. Excess cardiovascular risks were well recognized in patients with AS and were attributed to prolonged systemic inflammation. Uveitis is one of the most common extra-articular symptoms of AS and is also considered an indicator of systemic inflammation. This study aimed to investigate whether uveitis was a risk factor for developing acute myocardial infarction (AMI) in patients with AS using the National Health Insurance Research Database (NHIRD). Methods: Data were collected from the NHIRD over a fifteen-year period. Variables were analyzed using the Pearson chi-square test and Fisher’s exact test. Risk factors for the occurrence of AMI were examined by calculating hazard ratio. Kaplan-Meier analysis was performed to compare the cumulative incidence of AMI in the uveitis and non-uveitis cohorts. Results: A total of 5905 patients with AS were enrolled, including 1181 patients with uveitis (20%) and 4724 patients without uveitis (80%). The Kaplan–Meier method with the log-rank test showed that the uveitis group had a significantly higher cumulative hazard for patients with AMI than the non-uveitis group (p < 0.001). The adjusted hazard ratio (aHR) of AMI was higher in the uveitis group than in the non-uveitis group (aHR = 1.653, p < 0.001). Stratified analysis revealed that patients with uveitis had an increased risk of developing AMI regardless of their sex (male/female aHR = 1.688/1.608, p < 0.001). Patients with uveitis in all age groups were independently associated with an increased risk of developing AMI compared to those without uveitis (20–39 years/40–59 years/≥ 60 years, adjusted HR = 1.550, 1.579, 3.240, p < 0.001). Patients with uveitis had a higher probability of developing AMI regardless of comorbidities. Patients with uveitis and other comorbidities were more predisposed to AMI than patients with uveitis only. Conclusion: Uveitis is a significant risk factor for developing AMI in patients with AS. Physicians should be aware of the potential cardiovascular risk in AS patients with uveitis, especially simultaneously with other traditional risk factors of AMI. Further prospective studies are needed to elucidate the underlying mechanism between uveitis and AMI in patients with AS.